THE EFFECTIVENESS OF SURGICAL TREATMENT IN GASTRIC NEOPLASMS: AN INTEGRATIVE REVIEW (CIPEEX, 2025)
INTRODUCTION: Gastric cancer has various manifestations in the human body, one of which is lymph node rigidity, used as a prognostic indicator. Treatment differentiation is based on the type of cancer and its metastatic level; however, high metastasis cases are managed with palliative treatments, while oligometastatic cases are approached with chemotherapeutic/radiotherapeutic methods followed by surgical intervention through gastric resection and associated lymph node removal. Despite this, scientific evidence shows complications that can occur during the procedure and a high rate of tumor recurrence after such surgical treatments. OBJECTIVE: To analyze the effectiveness of surgical intervention in cases of gastric neoplasms. METHODOLOGY: This is an integrative review, with data collected from Scielo and Medline databases in May 2024, using descriptors "effectiveness," "treatment," and "gastric neoplasia," with the Boolean operators "and" between them and "not" for literature review. Articles in English and Portuguese published in the last 10 years were selected. Discrepant literature was excluded. RESULTS: Effectiveness rates suggest that lymph node resection and gastric surgery, while more effective compared to traditional palliative treatment, still have negative manifestations with elevated indices. "Failure to rescue (FTR)," a qualitative assessment parameter in surgical cases that result in death, shows that besides high recurrence rates, there are significant surgical complications leading to death. It is worth noting that patients who recover from complications are still subject to cancer recurrence rates. CONCLUSION: The evolution in the treatment of gastric neoplasms is notable with surgical application, as this approach can extend the survival of oncology patients. However, it has median effectiveness rates due to complications, recurrence, and metastasis that were previously unobserved, necessitating the analysis of cellular markers and systemic evaluations to determine real efficacy, considering the specificity of each case.
Keywords: effectiveness; gastric neoplasia; treatment